Wskaźniki trwałego rozwoju: spojrzenie ekonomisty - Żylicz, Tomasz (Sustainability indicators: an economist's view, 2007)
The paper outlines a design of the GDP modified in order to take into account factors relevant for sustainability, and especially those that highlight the role of the natural environment. The aim of the author was to show that such an index is consistent with the economic understanding of sustainable deyelopment (as implied by the classical Brundtland definition), and it captures better than others the ability of an economy to meet both the present and the futurę needs. The argument is based on the Bergson-Samuelson social welfare function approximated by the modified GDP index.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 89-98